Gold and Oil Prices: Abnormal Returns, Momentum and Contrarian Effects - Guglielmo Maria Caporale; Alex Plastun (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper explores price (momentum and contrarian) effects on the days characterised by abnormal returns and the following ones in two commodity markets. Specifically, using daily Gold and Oil price data over the period 01.01.2009-31.03.2020 the following hypotheses are tested: H1) there are price effects on days with abnormal returns, H2) there are price effects on the day after abnormal returns occur; H3) the price effects caused by abnormal returns are exploitable. For these purposes average analysis, t-tests, CAR and trading simulation approaches are used. The main results can be summarised as follows. Hourly returns during the day of abnormal returns are significantly bigger than those during average “normal” days. Prices tend to move in the direction of abnormal returns till the end of the day when these occur. The presence of abnormal returns can usually be detected before the end of the day by estimating specific timing parameters, and a momentum effect can be detected. On the following day two different price patterns are detected: a momentum effect for Oil prices and a contrarian effect for Gold prices respectively. Trading simulations show that these effects can be exploited to generate abnormal profits.
Keywords: G12; G17; C63; 330; commodities; anomalies; momentum effect; contrarian effect; abnormal returns